The microRNA-381(miR-381)/Spindlin1(SPIN1) axis contributes to cell proliferation and invasion of colorectal cancer cells by regulating the Wnt/β-catenin pathway. Issue 2 (20th December 2021) - Zhou, Ling; Wang, Heng; Fang, Zhi; Zhong, Min; He, Yan; Zou, Jianping; Huang, Shanshan; Li, Junhe; Xiang, Xiaojun; Fang, Ziling
ABSTRACT: Our study aimed to investigate the clinical significance and biological functions of Spindlin1 (SPIN1) in colorectal cancer (CRC) tumorigenesis and progression, as well as the mechanism underlying its upregulation. The expression of SPIN1 was detected by immunohistochemistry and western blotting assays. Bioinformatics prediction and dual-luciferase reporter assays were used to determine whether microRNA-381 (miR-381) could target SPIN1. A series of cell functional experiments were performed to investigate whether the miR-381-mediated regulation of SPIN1 is involved in the progression and aggressiveness of CRC cells via the Wnt/β-catenin pathway. Our results showed that SPIN1 is frequently overexpressed in CRC tissues and cell lines, and its upregulation is positively correlated with disease progression and lymph node metastasis. Moreover, SPIN1 depletion suppresses cell growth, migration, and invasion through inactivation of the Wnt/β-catenin signaling pathway, which recapitulates the effects of miR-381 upregulation. Moreover, SPIN1 is a target gene of miR-381, and miR-381 is downregulated in CRC. Furthermore, the reintroduction of SPIN1 partially abolished the miR-381-mediated inhibitory effects in CRC cells. In summary, our data revealed that the miR-381/SPIN1 axis greatly contributes to CRC tumorigenesis by orchestrating the Wnt/β-catenin pathway, thereby representing actionable therapeutic targets for colorectal cancer patients.